The application of virtual reality meditation and mind–body exercises among older adults - Gao, Dong; Su, Yuqin; Zhang, Xing; Li, Hansen; Luo, Hongcheng (Frontiers in Psychology, 2024)
Virtual Reality (VR)-based mindfulness is a promising method to improve the health of older adults. Therefore, many attempts have been made to explore the application of VR-based mindfulness, such as VR meditation and mind-body exercises, in older adults. Generally, current studies indicate the heavy reliance on apparatus for implementing VR-based mindfulness interventions. In VR meditation, the crucial apparatus is VR headsets. In VR mind-body exercises, three essential components are required: motion capture sensors, main consoles, and display screens. In the aspect of health promotion, VR meditation is an effective method for improving mental health, pain, and quality of life in older adults. VR mind-body exercises contribute to increasing the mental health and physical function of older adults. Furthermore, VR mind-body exercises may be combined with other forms of exercise as a mixed method to promote the health of older adults. VR-based mindfulness interventions enhance the meditation and mind-body exercises experience for older adults while improving accessibility. However, their implementation still encounters a series of challenges, such as cost, technical anxiety, and apparatus-related issues. Additionally, we recommend future research to examine the optimal exercise dose for VR mind-body exercises to maximize their health benefits.